Empowering Farmer Communities through Coffee Husk Utilization: Training on Organic Fertilizer and Fermented Livestock Feed Production in Desa Wanagiri, Bali - Suriati, Luh; Kaca, Nyoman; Wirajaya, Anak Agung Ngurah Mayun; Damayanti, Putu Sulis Dewi; Rabani, I Gusti Agung Yogi; Damayanti, Ni Luh Suriati Putu Sulis Dewi; Chindrawati, Anak Agung Sagung Manik; Putri, Putu Ananda Icaka; Putra, I Putu Ajus Raditya; Padmarini, Ni Made Andira; Darmawan, Kadek Dinda Rahayu; Dewi, Ni Made Putri Pradnya Paramita (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
The increasing volume of coffee husk waste in rural production centers has become a major challenge for environmental sustainability. In Desa Wanagiri, Bali, coffee processing generates large amounts of husks that are often discarded or burned, resulting in soil and water pollution. This community empowerment program was designed to transform coffee husks into valuable products through training and practice on organic fertilizer production and fermented livestock feed formulation. The activities were carried out in three integrated stages: preparation, training and practice, and mentoring and evaluation. Farmer groups were trained to produce organic compost using bio-activators and to formulate fermented feed from coffee husks enriched with bran and mineral supplements. The results indicate that 100% of participants successfully applied the techniques, with 90–95% retaining the knowledge delivered during training. Approximately 95% of farmers tested fermented feed on their livestock and confirmed its safety, while 90% applied compost to their crops and observed improvements in soil structure and plant growth. Despite some technical challenges, all respondents expressed a strong commitment to continuing the practices. Beyond technical outcomes, the program fostered knowledge sharing, increased community cohesion, and opened opportunities for additional household income. Contribution to Sustainable Development Goals (SDGs):SDG 2 - Zero Hunger SDG 12 - Responsible Consumption and Production SDG 15- Life on Land